Recomendações de design para jogos educacionais Inclusivos para diferentes dispositivos - Reis, Ana Paula de Sousa (2020)
In the last decades, digital games have invaded people daily lives. The increasingly fast and accessible Internet, combined with the popularization of mobile devices, have promoted the growth of the digital games market, previously restricted to the consoles and desktops now are spread out on smartphones and tablets screens. This reality reached the school environment and digital educational games emerged, with resources capable of bringing an active, fun and immersive learning to the school environment, in addition to allowing content to become accessible inside and outside the classroom. However, considering these resources are predominantly graphic, most games exclude people with visual impairments. The aim of this work is to propose a set of recommendations for the design of educational games for different devices, including people with visual impairments. To this end, a literature review was conducted and two sets of recommendations were found and served as the basis for this study: EduGameAccess (Fontoura Junior, 2018), which includes recommendations for design of inclusive educational games and Korhonen’s set (2016), which includes recommendations for design of games for mobile devices. The two sets were analyzed and adapted, resulting in an initial recommendation set for the design of inclusive educational games for different devices. This initial set was evaluated and tested in the design and development process of the educational game A Era Inclusiva, developed by the Laboratório de Objetos de Aprendizagem (LOA), which made it possible the set reﬁnement. To improve and validate the initial set, a case study was conducted, based on the adaptation of the game Forca, developed by LOA, using the proposed set, resulting in the Forca Inclusiva game. Iterative cycles of design, development and evaluation were carried out and the ﬁnal version of the game and the proposed recommendation set, called EduGameAccessM was obtained, containing 39 recommendations. The game ﬁnal version conformance with EduGameAccess-M was evaluated by specialists and developers. In addition, playability tests and EgameFlow questionnaire were applied with four group of users (blind, color blind, low vision and no visual impairment) to evaluate the target audience experience with the obtained game. The results indicates that EduGameAccess-M can be effective in the design of an inclusive educational game for desktop and mobile devices.